2020
DOI: 10.20885/jsb.vol24.iss1.art6
|View full text |Cite
|
Sign up to set email alerts
|

Financial behaviour and financial wellbeing of MSMEs actors: The role of financial literacy and cognitive factors

Abstract: That financial literacy and psychological characteristics are important determinants of financial decisions have long been recognized in the literature. By focusing on Micro Small Medium Enterprises (MSMEs), this study investigates the extent to which financial behaviour and financial well-being consisting of both financial security and financial anxiety can be explained by financial literacy and cognitive factors such as self-control, optimism, and deliberative thinking. Several demographic factors such as ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Research has shown that the longer the involvement of MSMEs, the higher the level of financial literacy (Aeni & Innayah, 2022). In addition, the level of education has also been identified as a factor that influences the application of accounting in the preparation of financial reports, indicating a relationship between education and financial literacy (Rafik & Rahayu, 2020). These findings suggest that as MSMEs gain more experience and knowledge through their years of work and education, their financial literacy increases.…”
Section: Factors Influencing the Level Of Financial Literacymentioning
confidence: 88%
See 1 more Smart Citation
“…Research has shown that the longer the involvement of MSMEs, the higher the level of financial literacy (Aeni & Innayah, 2022). In addition, the level of education has also been identified as a factor that influences the application of accounting in the preparation of financial reports, indicating a relationship between education and financial literacy (Rafik & Rahayu, 2020). These findings suggest that as MSMEs gain more experience and knowledge through their years of work and education, their financial literacy increases.…”
Section: Factors Influencing the Level Of Financial Literacymentioning
confidence: 88%
“…In contrast to research (Suryanto & Rasmini, 2018) found that age had no effect on literacy levels finance among MSMEs in Bandung. These findings suggest that age may have varying effects on MSME financial literacy, depending on the specific context and demographic characteristics of MSME actors (Rafik & Rahayu, 2020).…”
Section: Factors Influencing the Level Of Financial Literacymentioning
confidence: 88%
“…Furthermore, employee performance is also influenced by financial literacy because of some reasons. First, by having good literacy on financial, an employee will be more focus on his/her performance, (Rafik & Rahayu, 2020). Second, financial literacy is a basic knowledge about financial that everyone should have to earn a good job performance, (Eliza & Susanti, 2020).…”
Section: F Testmentioning
confidence: 99%
“… Budget preparation,  Understanding the effect of inflation and understanding how to access finance at minimum cost, among others (Ibrahim, 2017;Patrick, 2015) Ismail et al (2017 highlighted that managers with very high levels of financial behavior are more inclined to make good use of their organization's financial resources, such as effectively controlling the inflow and outflow of money. For example, Rafik & Rahayu (2020) noted that the preparation of an effective budget is highly dependent on proper bookkeeping, which also provides businesses with the opportunity to be able to pay their obligations on time and also collect their debts within a reasonable time frame. Financial education is the major factor determining an individual's financial behavior level in managing financial resources.…”
Section: Competency Theorymentioning
confidence: 99%